Calendar anomalies in the Ukrainian stock market - Guglielmo Maria Caporale; Alex Plastun (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This paper is a comprehensive investigation of calendar anomalies in the Ukrainian stock market. It employs various statistical techniques (average analysis, Student's t-test, ANOVA, the Kruskal-Wallis test, and regression analysis with dummy variables) and a trading simulation approach to test for the presence of the following anomalies: Day of the Week Effect; Turn of the Month Effect; Turn of the Year Effect; Month of the Year Effect; January Effect; Holiday Effect; HalloweenEffect. The results suggest that in general calendar anomalies are not present in the Ukrainian stock market, but there are a few exceptions, i.e. the Turn of the Year and Halloween Effect for the PFTS index, and the Month of the Year Effect for UX futures. However, the trading simulation analysis shows that only trading strategies based on the Turn of the Year Effect for the PFTS index and the Month of the Year Effect for the UX futures can generate exploitable profit opportunities that can be interpreted as evidence against market efficiency.
Keywords: G12; C63; 330; Calendar Anomalies; Day of the Week Effect; Turn of the Month Effect; Month of the Year Effect; January Effect; Holiday Effect; Halloween Effect